A cross-national examination of sexual desire: The roles of 'gendered cultural scripts' and 'sexual pleasure' in predicting heterosexual women's desire for sex. (1st December 2019) - Rubin, Jennifer D.; Conley, Terri D.; Klein, Verena; Liu, Jie; Lehane, Christine M.; Dammeyer, Jesper
Abstract: Women's low sexual desire has received a great deal of cultural and research attention. Surprisingly, pleasure women receive during partnered sexual encounters and sociocultural beliefs about sexual desire have largely been absent in the literature. The present study examined if gendered cultural scripts and pleasure from a sexual encounter predicted heterosexual women's desire for sex in four cross-national samples: United States ( N  = 741), Canada ( N  = 391), Germany ( N  = 220), and Denmark ( N  = 128). Hierarchical multiple regression results indicate that for United States, Canadian, and German samples, anticipated pleasure and orgasm centrality were significant predictors of desire for sex, while endorsement of gendered cultural scripts was a significant predictor of lower desire for sex. For the Danish sample, only endorsement of gendered cultural scripts was a robust predictor of lower desire for sex. Follow-up analyses using multilevel modeling found that the relationship between the predictor variables and desire for sex was not significantly different across samples. Findings suggest that nations may share more similarities than differences within the domain of sexual desire—heterosexual women that prioritize sexual pleasure and eschew gendered cultural scripts may be more likely to desire sex.